1997
DOI: 10.1074/jbc.272.45.28187
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Neuronal Nitric-oxide Synthase with Caveolin-3 in Skeletal Muscle

Abstract: Neuronal nitric-oxide synthase (nNOS) has been shown previously to interact with ␣ 1 -syntrophin in the dystrophin complex of skeletal muscle. In the present study, we have examined whether nNOS also interacts with caveolin-3 in skeletal muscle. nNOS and caveolin-3 are coimmunoprecipitated from rat skeletal muscle homogenates by antibodies directed against either of the two proteins. Synthetic peptides corresponding to the membrane-proximal caveolin-3 residues 65-84 and 109 -130 and homologous caveolin-1 resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
128
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(137 citation statements)
references
References 28 publications
(38 reference statements)
7
128
2
Order By: Relevance
“…We found, however, no evidence of increased expression or altered interaction of caveolins with NOS enzymes in muscle of STZ-diabetic rats. Unlike a previous study where nNOS was shown to coimmunoprecipitate with caveolin-3 in skeletal muscle [30], we could not detect any association of these two proteins in our study. Caveolin-3 immunoprecipitation was done in the presence of several different detergents [octylglucoside, Triton X-100, or 3-[(3-cholamidopropyl)-dimethylammonio]-1-propanesulphonate (CHAPS)] with similar results (data not shown).…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…We found, however, no evidence of increased expression or altered interaction of caveolins with NOS enzymes in muscle of STZ-diabetic rats. Unlike a previous study where nNOS was shown to coimmunoprecipitate with caveolin-3 in skeletal muscle [30], we could not detect any association of these two proteins in our study. Caveolin-3 immunoprecipitation was done in the presence of several different detergents [octylglucoside, Triton X-100, or 3-[(3-cholamidopropyl)-dimethylammonio]-1-propanesulphonate (CHAPS)] with similar results (data not shown).…”
Section: Discussioncontrasting
confidence: 55%
“…The lack of detectable nNOS-caveolin-3 interaction cannot be explained by the limit of detection of nNOS or eNOS by immunoblotting because caveolin-3 was quantifiably immunoprecipitated from up to 400 mg of the CSM fraction and NOS enzymes can be readily detected from 10 mg of CSM membranes. One possible explanation is that in the previous study [30] caveolin-3 was immunoprecipitated from total muscle homogenates whereas we have used semi-purified CSM fractions as starting material. It is possible that the interaction between nNOS and caveolin-3 is specifically localised to some cellular compartments (e. g. cytoskeletal elements) not isolated by our fractionation procedure.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…40 Activity of all 3 NOS isoforms is modulated by proteinprotein interactions. 41 Protein inhibitor of neuronal NOS (PIN), 42,43 caveolin-1, 44 caveolin-3, 45 and several proteins bearing PDZ domains 46 that influence targeting to discrete membrane domains of excitable tissues regulate NOS 1 activity. Although some of these proteins have been localized to the kidney, 47 we know of no studies investigating the role of these proteins in renal NOS 1 activity.…”
Section: Regulation Of Nos Activitymentioning
confidence: 99%
“…CAV-1 has been reported to negatively regulate the downstream activation of many signaling molecules, including the EGFR, Src family tyrosine kinases, and components of the Ras/MAP kinase pathway (26,27). There was a higher IHC expression of baseline CAV-1 staining in the tumors (P281 and P247) sensitive to bosutinib compared with resistant tumors (P215 and P420), and bosutinib treatment augmented the CAV-1 expression in sensitive cases compared with untreated tumors (Fig.…”
Section: Cav-1 Expression In Tumor Xenografts By Reverse Transcriptiomentioning
confidence: 80%